Effect of Soybean (Glicyne max (L.) Merill) with Lamtoro Gung (Leucaena leucocephala) Proportion on the Characteristics of Soy Milk - Ramadhania, Rizky Laila; Saidi, Ida Agustini; Nurbaya, Syarifa Ramadhani; Machfudz, Al (Universitas Ahmad Dahlan, 2023)
The utilization of soy milk is an alternative for people with lactose intolerance. Soy milk can be made with lamtoro gung substitution because the nutritional content of lamtoro gung is close to soybeans. This research aimed to determine the effect of soybean/lamtoro gung proportion on the characteristics of soy milk. This research was conducted from May until July 2022. The experimental study used a randomized block design with the treatment were soybean (K) with lamtoro gung (L) proportion S1 (K 100%: L 0%), S2 (K 95%: L 5%), S3 (K 90%: L 10%), S4 (K 85%: L 15%), S5 (K 80: L 20%), S6 (K 75%: L25), S7 (K 70%: L 30%) S8 (K 65%: L 35%), and S9 (K 60%: L 40%). The data obtained were then analyzed using analysis of variance and further test BNJ 5%, the organoleptic test used Friedman test, and determine the best treatment used effectiveness index. The results showed a significant effect of soybean with lamtoro gung proportion on protein content, vitamin C content, vitamin A content, pH, viscosity, TDS, and hedonic test of aroma and taste. The best treatment was S3 (soybean 90%: lamtoro 10% with characteristics of protein content 3.304%, vitamin C content 0.291%, vitamin A content 2.239 mg/g, pH 5.917, viscosity 3.533×103 mPa.s, TDS 7.833 °brix, and hedonic test of color 3.40, aroma 3.30, taste 3.40, and texture 3.20. This study contributes to evaluate the soy milk characteristics from soybean and lamtoro gung.